Analysis of Conceptual Readiness in Chemical Bonding Concepts among Pre-Service Chemistry Teachers Using a Three-Tier Diagnostic Test - Allika Haya Fahrunisa; Nahadi Nahadi; Soja Siti Fatimah (Universal Education, 2025)
The conceptual readiness of pre-service chemistry teachers regarding chemical bonding plays a crucial role in supporting pedagogical competence and deep content understanding. This study aims to analyze the level of students’ conceptual readiness in understanding chemical bonding concepts using a three-tier diagnostic test. A qualitative research method with a descriptive approach was employed, involving 27 students from the chemistry education program at a private university in North Sumatra. The results indicate that most students are at a partial understanding level, with a dominance of misconceptions particularly in concepts such as ionic bonding, compound polarity, and valence bond theory. These findings highlight the urgent need to strengthen pedagogical strategies and enhance instructional design to improve conceptual literacy and prepare future teachers to face the challenges of 21st-century science education. The study recommends the integration of diagnostic assessment into teacher education curricula to support the development of chemistry instruction that is conceptually grounded and sustainability-oriented.